Measurement of radius of a metallic ball using eddy current testing based on peak frequency difference feature. (November 2021) - Hu, Gang; Huang, Ruochen; Lu, Mingyang; Zhou, Lei; Yin, Wuliang
Highlights: The peak frequency is linear to the lift-offs between the centre of coil and ball. The slope of peak frequencies versus lift-offs is linked to the radius of ball. The radius of the metallic ball can be deduced by using the measured slope. The radius of the metallic ball is retrieved with an error of less than 2%. Abstract: This paper proposes a linear eddy-current feature to determine the radius of a metallic ball in a non-contact manner. An electromagnetic eddy-current sensor with two coils is placed co-axially to the metal ball during measurement. It is well known that the distance between the sensor and test piece (i.e. lift-off) affects eddy-current signals. In this paper, it is found that the peak frequency feature of inductance spectrum is linear to the lift-off spacing between the centre of coil and ball. Besides, the slope of peak frequencies versus lift-offs is linked to the radius of ball. The radius of metallic balls is retrieved from the experimental and embedded analytical result of the slope. Measurements have been carried out on 6 metallic balls with different radii. The radius of the metallic ball can be retrieved with an error of less than 2%.